THE METHODOLOGY OF COST MANAGEMENT IN THE MODERN SOCIETY - P. Labzunov (Российский технологический журнал)
The transformation of the market economy in the conditions of information society causes the necessity of development of cost management contemporary methodology. The formation of an effective system is possible only on the basis adapted to the innovative development of the principles and methods of management. These basic elements of the methodology need to be clarified. In connection with the transition to the market relations in the Russian economy the radical changes occurred: the form of property and owners changed in the majority of economic subjects; the whole system of productive-public relations was transformed; passage from planning and directive management to the competition methods and the self-regulation on a scale of the national economy occurred. At the same time scientific base of cost management, which industry enterprises use, both domestic and borrowed from the western scientific schools of management, is out-moded. The top-down administrative system for industrial enterprises' activity and cost management, which functioned in the USSR, is destroyed even in the 90's of past century, and industrial enterprises, large companies preserved only the separate elements of cost management system, they mainly use the methods of limitation and expenditures control, while the integrated system for expenditures management is necessary. The need for organising the comprehensive system for cost management requires renovation and development of methodological base. Contemporary society is increasingly more frequently defined as information-based, so this circumstance gives new quality both to production and to management, increases management capabilities everywhere and by the enterprises' economic activity in particular. But one must take into account, that the improvement of scientific base and management practice doesn't occur simultaneously, but represents the complex process of formatting, approbation and management system organizing, is exercised gradually. Substantial changes in the conditions and the nature of production, administrative processes determine the need of tasks' refining, continuous renovation and improvement of the methodological base of cost management.